(untitled) (Swiss Medical Weekly, 2016)
QUESTION UNDER STUDY: In Switzerland, summer 2015 was the second warmest summer for 150 years (after summer 2003). For summer 2003, a 6.9% excess mortality was estimated for Switzerland, which corresponded to 975 extra deaths. The impact of the heat in summer 2015 in Switzerland has not so far been evaluated. METHODS: Daily age group-, gender- and region-specific all-cause excess mortality during summer (June–August) 2015 was estimated, based on predictions derived from quasi-Poisson regression models fitted to the daily mortality data for the 10 previous years. Estimates of excess mortality were derived for 1 June to 31 August, at national and regional level, as well as by month and for specific heat episodes identified in summer 2015 by use of seven different definitions. RESULTS: 804 excess deaths (5.4%, 95% confidence interval [CI] 3.0‒7.9%) were estimated for summer 2015 compared with previous summers, with the highest percentage obtained for July (11.6%, 95% CI 3.7‒19.4%). Seventy-seven percent of deaths occurred in people aged 75 years and older. Ticino (10.3%, 95% CI −1.8‒22.4%), Northwestern Switzerland (9.5%, 95% CI 2.7‒16.3%) and Espace Mittelland (8.9%, 95% CI 3.7‒14.1%) showed highest excess mortality during this three-month period, whereas fewer deaths than expected (−3.3%, 95% CI −9.2‒2.6%) were observed in Eastern Switzerland, the coldest region. The largest excess estimate of 23.7% was obtained during days when both maximum apparent and minimum night-time temperature reached extreme values (+32 and +20 °C, respectively), with 31.0% extra deaths for periods of three days or more. CONCLUSIONS: Heat during summer 2015 was associated with an increase in mortality in the warmer regions of Switzerland and it mainly affected older people. Estimates for 2015 were only a little lower compared to those of summer 2003, indicating that mitigation measures to prevent heat-related mortality in Switzerland have not become noticeably effective in the last 10 years.